Tracheal intubation without muscle relaxants: a randomized study of remifentanil or alfentanil in combination with thiopental - Safavi, Mohammadreza (Ann Saudi Med, 2008)
BACKGROUND AND OBJECTIVE: The combination of alfentanil-propofol or remifentanil-propofol provides adequate conditions for tracheal intubation without neuromuscular blocking drugs in most patients, but hypotension can occur during induction of anesthesia with propofol. We compared clinically acceptable intubating conditions and cardiovascular responses to induction and endotracheal intubation in patients receiving either alfentanil 40 μg/kg or remifentanil 2, 3 or 4 μg/kg, followed by thiopental 5 mg/kg. PATIENTS AND METHODS: In a randomized trial, 80 patients were assigned in equal numbers to one of four groups: remifentanil 2, 3, or 4 μg/kg (groups R2, R3, R4, respectively) or alfentanil 40 μg/kg (group A40). In each group, the injection was given over 90 seconds followed by thiopental 5 mg/kg. Ninety seconds after the administration of thiopental, laryngoscopy and intubation were attempted. Intubating conditions were assessed as excellent, satisfactory, fair, or unsatisfactory. Arterial blood pressure and heart rate changes accompanying the four induction techniques were also recorded. RESULTS: Overall conditions at intubation were significantly better (P<.05), and the frequency of excellent conditions was significantly higher (P<.05) in the R4 or A40 group compared with the R2 or R3 group. Intubating conditions were not significantly different between group R4 and A40 (P>.05). The highest dose of remifentanil (4μg/kg) resulted in an 18.7% decrease in mean arterial pressure (MAP) after induction of anesthesia compared with a 16.4% decrease in MAP with alfentanil 40 μg/kg (difference not statistically significant). CONCLUSION: The administration of remifentanil 4 μg/kg or alfentanil 40 μg/kg before thiopental 5 mg/kg provided good to excellent conditions for endotracheal intubation with acceptable hemodynamic changes.